On the problem of interrelations between generations - Bajoriūnas , Z. (Psichologija, 1971)
The analysis of some ideas expressed by foreign scientists on the problem of the education of the young generation and of juvenile delinquency has been taken as a basis for the present work. The article points out that certain scientists in the capitalist countries attempt to regard the conflict of generations which exists in the bourgeois society as the main and only cause for the growth of juvenile delinquency and deterioration in youth behaviour. In the opinion of bourgeois ideologists the conflict of generations is not dependent on the social and political structure of the class society - it is rather a universal phenomenon which has been –effected by a rapid development of technology, science and education. Adhering to this opinion, certain authors in the capitalist countries try to conceal the main cause which lies in the capitalist way of production and the corresponding production relations and which brings about deterioration of youth behaviour and increase of juvenile delinquencies. The author compares this un-Marxist approach to the problem of generations with the Marxist solution of the problem which has been tackled by a number of scientists in the socialist countries. The comparative analysis of works by foreign scientists serves as a basis for the author’s attitude towards the problem of interrelations between generations.